Whole‐life embodied carbon in multistory buildings: Steel, concrete and timber structures. - Hart, Jim; D'Amico, Bernardino; Pomponi, Francesco (Journal of Industrial Ecology, 2021)
Buildings and the construction industry are top contributors to climate change, and structures account for the largest share of the upfront greenhouse gas emissions. While a body of research exists into such emissions, a systematic comparison of multiple building structures in steel, concrete, and timber alternatives is missing. In this article, comparisons are made between mass and whole‐life embodied carbon (WLEC) emissions of building superstructures using identical frame configurations in steel, reinforced concrete, and engineered timber frames. These are assessed and compared for 127 different frame configurations, from 2 to 19 stories. Embodied carbon coefficients for each material and life cycle stage are represented by probability density functions to capture the uncertainty inherent in life cycle assessment. Normalized results show clear differences between the masses of the three structural typologies, with the concrete frame approximately five times the mass of the timber frame, and 50% higher than the steel frame. The WLEC emissions are mainly governed by the upfront emissions (cradle to practical completion), but subsequent emissions are still significant—particularly in the case of timber for which 36% of emissions, on average, occur post‐construction. Results for WLEC are more closely grouped than for masses, with median values for the timber frame, concrete frame, and steel frame of 119, 185, and 228 kgCO2e/m2, respectively. Despite the advantage for timber in this comparison, there is overlap between the results distributions, meaning that close attention to efficient design and procurement is essential. This article met the requirements for a gold–gold JIE data openness badge described in http://jie.click/badges.